2007
DOI: 10.1103/physrevlett.99.217406
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Electron Delocalization in Liquid Water and Ice at Attosecond Time Scales

Abstract: We determine electron delocalization rates in liquid water and ice using core-hole decay spectroscopy. The hydrogen-bonded network delocalizes the electrons in less than 500 as. Broken or weak hydrogen bonds--in the liquid or at the surface of ice--provide states where the electron remains localized longer than 20 fs. These asymmetrically bonded water species provide electron traps, acting as a strong precursor channel to the hydrated electron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
125
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(131 citation statements)
references
References 44 publications
5
125
1
Order By: Relevance
“…Two recent, independent measurements of the spectator Auger-electron spectrum of liquid water show experimentally that the electron becomes increasingly delocalized as the excitation energy increases. 33,62 Even for the lowest excited state of condensed water, Hahn et al 34 showed that the excited electron is somewhat delocalized onto neighboring molecules, although the excited state is still located primarily on a single water molecule.…”
Section: Fate Of Gas-phase Excited States In Liquid Water and Tentmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent, independent measurements of the spectator Auger-electron spectrum of liquid water show experimentally that the electron becomes increasingly delocalized as the excitation energy increases. 33,62 Even for the lowest excited state of condensed water, Hahn et al 34 showed that the excited electron is somewhat delocalized onto neighboring molecules, although the excited state is still located primarily on a single water molecule.…”
Section: Fate Of Gas-phase Excited States In Liquid Water and Tentmentioning
confidence: 99%
“…31 An alternate view is one in which the excited molecular orbitals are partially delocalized over one or more neighboring solvent molecules. [32][33][34][35][36] Unfortunately, a clear and consistent theoretical description of the electronically excited states of liquid water is not yet available because accurate electronic structure calculations are extremely difficult for such strongly interacting molecules. [34][35][36][37][38][39][40][41] 2PA spectroscopy provides a new window on the electronic transitions of liquid water because the symmetry selection rules are different than for linear spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…In the excitation spectra, peak 1 appears at somewhat larger KEs due to spectator energy shifts, an effect which previously has been discussed for water in great detail. [41][42] For core-level ionization and excitation the spectral changes between normal and deuterated water are fairly similar; compare the respective differential spectra. Proton dynamics thus seems to be of importance for decays from all intermediate states reached throughout the O1s near-edge absorption fine structure of liquid water (here the delocalized two-hole final state contains an additional excited electron; 1e1h•1h).…”
Section: Core-level Excitation Induced Autoionization Spectra: H 2 O(mentioning
confidence: 99%
“…Here, an electron from the occupied valence levels fills the core hole. The excess energy is transferred to a second electron (Auger electron) from the valence levels, which leaves the molecule with a kinetic energy of about 500 eV [25]. The Auger electron then scatters elastically as well as inelastically at surrounding water molecules (Auger cascade).…”
mentioning
confidence: 99%